Pengembangan Aplikasi Pengelolaan Usaha Berbasis Web Dengan Menggunakan Prototyping (Studi Kasus : UKM Krupuk Jaya) - Faizal Bachtiar; Agi Putra Kharisma; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
UKM Krupuk Jaya is a small and medium business that focuses on the marketing of crackers. Everyday UKM Krupuk Jaya produce 26,000 pcs crackers which are marketed to places around Malang. However, in UKM Krupuk Jaya the management of business data still uses conventional methods so that errors often occur in the processing of the number of orders ordered by sales, resulting in differences in the number of products ordered. And there is no information about raw materials that result in cancellation of orders by the owner when a sudden order by the sales because there is no availability of raw materials. In the process of calculating business profits, errors often occur resulting in inaccurate reporting. With the problems that arise in UKM Krupuk Jaya, research is carried out by developing a web-based business management application that can help in the management of UKM Krupuk Jaya. This research was conducted with the stages of engineering needs, design, implementation and testing. At the engineering stage needs 43 functional requirements and 1 non-functional needs. at the implementation stage using a web programming language and using a MySQL database. In the testing phase, it is done by using 4 test methods, Unit testing, integration testing, validation testing yields 100% valid and usability testing produces value 79,45 so that the system belongs to the acceptable category.